Carbon loss from northern circumpolar permafrost soils amplified by rhizosphere priming - Keuper, Frida; Wild, Birgit; Kummu, Matti; Beer, Christian; Blume-Werry, Gesche; Fontaine, Sébastien; Gavazov, Konstantin; Gentsch, Norman; Guggenberger, Georg; Hugelius, Gustaf; Jalava, Mika; Koven, Charles; et al. (Nature Geoscience, 2020)
International audience As global temperatures continue to rise, a key uncertainty of climate projections is the microbial decomposition of vast organic carbon stocks in thawing permafrost soils. Decomposition rates can accelerate up to fourfold in the presence of plant roots, and this mechanism-termed the rhizosphere priming effect-may be especially relevant to thawing permafrost soils as rising temperatures also stimulate plant productivity in the Arctic. However, priming is currently not explicitly included in any model projections of future carbon losses from the permafrost area. Here, we combine high-resolution spatial and depth-resolved datasets of key plant and permafrost properties with empirical relationships of priming effects from living plants on microbial respiration. We show that rhizosphere priming amplifies overall soil respiration in permafrost-affected ecosystems by similar to 12%, which translates to a priming-induced absolute loss of similar to 40 Pg soil carbon from the northern permafrost area by 2100. Our findings highlight the need to include fine-scale ecological interactions in order to accurately predict large-scale greenhouse gas emissions, and suggest even tighter restrictions on the estimated 200 Pg anthropogenic carbon emission budget to keep global warming below 1.5 degrees C.